Pengaruh Sikap Budaya Kerja Dan Motivasi Kerja Terhadap Kompetensi Guru Di Sekolah Thama Vitya Mulniti Yala Selatan Thailand - Syuhadah Che Wae; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract A school is an educational organization that aims to frame the school's mission, manage teaching and learning, and train teachers as well as students to achieve the same goals. Nowadays, many schools identify the problem of